â€œThere Was A Countryâ€: The Reminiscence Of Nigeria-Biafra Civil War And Elitesâ€™ Perception Of Nation And Nationalism In Nigeria. - EKHATOR, Osaisonor Godfrey (Ethiopian Journal of Social Sciences, 2018)
Much debate and controversy dominate almost everydiscussion on the Nigerian civil war. The most recent could be described as an intellectual war and ethnocentrism. These were characteristics of the responses and reactions to the book, â€œTHERE WAS A COUNTRYâ€¦â€ by Chinua Achebe. Over the years, scholars and political analysts have written books narrating different versions of the civil war, from the remote to immediate causes of the bloody thirty months war. To some, these efforts are exaggerated accounts of the war; hence, they promote ethnic bigotry.Â  The question is how national integration can be achieved amidst continued ethnic dichotomy in Nigeria. Chinua Achebe has used his literary prowess to express in varying degree; the quantum of disappointment experienced by Nigerians due to ethnic cleavages. It is conspicuous that ethnic diversity has spurred criticisms to and underplayed the clarion call for nationalism by Achebeâ€™s memoir. This paper uses historical analysis with a synopsis of the book, â€œTHERE WAS A COUNTRYâ€, in the discussion of Chinua Achebeâ€™s conception of nationalism on account of the civil war. In this paper, I argue that the memories of the Nigeria-Biafra civil war disenchant the spirit of nationalism in Nigerians. They (the Nigerian masses), therefore, relying on the perception of their ethnic political elite are lead to pursue ethnic nationalism. In otherwise, the the massesâ€™ understanding of nationalism is dictated and based on the definition given to it by the political leaders .